Use of Observation Care in US Emergency Departments, 2001 to 2008 - Venkatesh, Arjun K.; Geisler, Benjamin P.; Gibson Chambers, Jennifer J.; Baugh, Christopher W.; Bohan, J. Stephen; Schuur, Jeremiah D. (PloS one, 2011)
Observation care is a core component of emergency care delivery, yet, the prevalence of emergency department (ED) observation units (OUs) and use of observation care after ED visits is unknown. Our objective was to describe the 1) prevalence of OUs in United States (US) hospitals, 2) clinical conditions most frequently evaluated with observation, and 3) patient and hospital characteristics associated with use of observation. Retrospective analysis of the proportion of hospitals with dedicated OUs and patient disposition after ED visit (discharge, inpatient admission or observation evaluation) using the National Hospital Ambulatory Medical Care Survey (NHAMCS) from 2001 to 2008. NHAMCS is an annual, national probability sample of ED visits to US hospitals conducted by the Center for Disease Control and Prevention. Logistic regression was used to assess hospital-level predictors of OU presence and polytomous logistic regression was used for patient-level predictors of visit disposition, each adjusted for multi-level sampling data. OU analysis was limited to 2007-2008. In 2007-2008, 34.1% of all EDs had a dedicated OU, of which 56.1% were under ED administrative control (EDOU). Between 2001 and 2008, ED visits resulting in a disposition to observation increased from 642,000 (0.60% of ED visits) to 2,318,000 (1.87%, p<.05). Chest pain was the most common reason for ED visit resulting in observation and the most common observation discharge diagnosis (19.1% and 17.1% of observation evaluations, respectively). In hospital-level adjusted analysis, hospital ownership status (non-profit or government), non-teaching status, and longer ED length of visit (>3.6 h) were predictive of OU presence. After patient-level adjustment, EDOU presence was associated with increased disposition to observation (OR 2.19). One-third of US hospitals have dedicated OUs and observation care is increasingly used for a range of clinical conditions. Further research is warranted to understand the quality, cost and efficiency of observation care.